TINGKAT PEMAHAMAN SISWA KELAS VI SEKOLAH DASAR NEGERI KEJAMBON 2 MENGENAI PERMAINAN BOLA BESAR SEPAK BOLA - Fakhrurozi, Zaza Afnindar; Gusna Abi Nugraha; Fathan Nurcahyo (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2025)
The objective of this research is to determine: the level of comprehension of the sixth grade students of SD Negeri Kejambon 2 (Kejambon 2 Elementary School) regarding the big ball football game. This research was a quantitative approach research with survey method. The research population was 22 sixth grade students of SD Negeri Kejambon 2. The sample size of the study used total sampling so that a sample of 22 students was obtained. The data was collected by multiple choice tests. Data analysis techniques used the descriptive analysis elaborated in the form of percentages.The results of this research indicate that the level of comprehension of the sixth grade students of SD Negeri Kejambon 2 on the big ball football game is as follows: 0 student (0 %) has a very good level of comprehension, 3 students (13,70%) are in the good level of comprehension, 9 students (40,90%) are in the moderate level of comprehension, 7 students (31,80%) are in the low level of comprehension, and 3 students (13,60%) are in the very low leve of comprehension.